Peran Aplikasi Schoology dalam Pembelajaran Flipped Classroom pada Materi Teks Anekdot - Rani Jayanti; Suesthi Rahayuningsih (Jurnal Pendidikan Edutama, 2020)
Abstract: Schoology Apps is a part of Learning Management System (LMS) that makes it easy for teachers and students to interact wherever and whenever in learning anecdote text. Anecdote text begins to be taught to high school students, especially the tenthgrade students in Curriculum 2013. The purpose of this study is to investigate the role of schoology apps to learn anecdote text in flipped classroom. This study is a library research that starts from 1) choosing a topic, 2) exploring information, 3) setting the focus of study, 4) preparing data sources, 5) preparing data presentation, and 6) preparing reports. This data is secondary data from national and international journals, Indonesian and international books. The data collection method uses the documentation method. Data validation technique uses data triangulation techniques. It is analyzed using a content analysis method. The results show that anecdote text materials are compiled into schoology apps and integrated with a flipped classroom model that refers to Bergmann & Sams theory. The conclusion of this study is that the schoology apps plays an important role in the flipped classroom, it can be seen from the use of schoology apps for students at home. When they are at home or anywhere in the sense of not being in the classroom learning, they can access the materials of anecdote text first. In addition, they can have direct discussion before the classroom learning begins through the schoology apps. Keyword: schoology apps, flipped classroom, anecdote text Abstrak: Aplikasi schoology merupakan bagian dari LMS yang mempermudah pendidik dan peserta didik berinterasi dimanapun dan kapanpun dalam mempelajari teks anekdot. Teks anekdot mulai diajarkan pada siswa menengah atas, khususnya kelas 10 kurikulum 2013. Tujuan penelitin ini adalah ingin mengetahui peran aplikasi schoology dalam pembelajaran flipped classroom pada materi teks anekdot. Penelitian ini merupakan penelitian studi pustaka (library research) dengan prosedur penelitian dimulai dari, 1) memilih topik, 2) mengeskplorasi informasi, 3) menetapkan fokus penelitian, 4) menyiapkan sumber data, 5) menyiapkan penyajian data, dan 6) menyusun laporan. Data penelitian ini adalah data sekunder yang bersumber dari jurnal nasional, jurnal internasional, buku terbitan Indonesia dan luar negeri. Metode pengumpulan data menggunakan metode dokumentasi. Teknik validasi data menggunakan teknik triangulasi data. Data dianalisis menggunakan content analysis. Hasil penelitian menunjukkan bahwa materi-materi teks anekdot disusun ke dalam aplikasi schoology dan selanjutnya diintergrasikan dengan model pembelajaran flipped classroom yang mengacu pada teori Bergmann & Sams. Simpulan penelitian ini adalah aplikasi schoology sangat berperan penting dalam model pembelajaran flipped classroom, peran tersebut dapat dilihat dari penggunaan aplikasi schoology bagi siswa ketika sedang di rumah. Ketika sedang di rumah atau di manapun dalam artian tidak sedang dalam pembelajaran di kelas, siswa dapat mengakses materi teks anekdot terlebih dahulu, selain itu, siswa dapat berdiskusi secara langsung sebelum pembelajaran dimulai melalui aplikasi schoology. Kata kunci: aplikasi schoology, flipped classroom, teks anekdot